Application of marketing audit of small businesses in Kazakhstan: identifying prospects and development - Turekhanova, A.; Smykova М. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The purpose of this research is to study small businesses in Kazakhstan and the impact of marketing audit on the effective development of small businesses. The competent use of marketing activities will help improve the growth of small businesses. To study the impact of marketing audit on the development of small businesses in Kazakhstan, marketing research was used in the form of a survey and in-depth interviews among entrepreneurs and employees of enterprises. The number of small enterprises grows slowly during the crisis period and it should be noted that a large number of small enterprises closed in the first years of their existence. The results of the research showed that enterprises use only the simplest methods of performance evaluation, most entrepreneurs either do not own marketing audit tools, or are focused only on solving basic short-term tasks, such as increasing sales. Conducted marketing research has shown a direct relationship between the growth of the company and the use of effective marketing controls, such as marketing audit. Interviews with small business owners show that companies with marketing control and flexible marketing tendencies have more growth prospects than a company in which the manager did not use marketing control.